Review on in-vitro amebocyte culture–a lesson learned from past - Sheikh, Hassan Ibrahim; John, Akbar; Ichwan, Solachuddin J. A.; Kassim, Zaleha; Yunus, Kamaruzzaman (Universiti Teknologi Malaysia, 2015)

(untitled)
Limulus Amebocyte Lysate (LAL/TAL) assay is the only standard test approved by the Food and Drug Administration (FDA) to quantify bacterial endotoxin in injectable drugs and implantable medical devices. At present, horseshoe crabs are the sole source of LAL/TAL. Biomedical companies harvest and bleed horseshoe crabs which lead to ≤30% post bleeding mortality. The continuity of this practices will eventually deplete wild stock and threat horseshoe crab’s population. Though, many alternative biosensors were developed to quantify endotoxins, they are not without limitations and some of them even need LAL/TAL as source detectors. Hence, the LAL/TAL industry in its current form has ethical, ecological, commercial and technical issues that make it unideal standard test. An alternative method of culturing amebocyte in tissue culture medium has been addressed in literature since last 4 decades. This paper will address the issues in amebocyte culture in-vitro based on the published literatures. The paper will also suggest the best source of amebocyte cells (gill, gill flaps, blood), culture mode (monolayer or suspension), culture media (Grace's Insect Medium, Leibovitz’s L-15 Medium, Modified Essential medium, Shields and Sang insect medium, TNM- FH Medium, RPMI 1640 medium) and best culture conditions (pH, temperature, osmolarity). This review will also emphasize on key elements in establishing a cell line for the continuous harvesting of amebocyte in-vitro.